2017
DOI: 10.1016/j.toxrep.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of methanolic Tanacetum parthenium extract on CCl4-induced liver damage in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 36 publications
10
53
2
1
Order By: Relevance
“…The etahnolic extract of C. oliviforme (Oe) could thus be considered as the most effective in reversing the harmful effect of CCl 4 -liver injury on ALT and AST raised levels when compared to the standard hepatoprotective drug, Silymarin with relative potencies 1.51 and 2.22, respectively ( Table 2). The raised activity of serum transaminases in CCl 4 intoxicated rats, as observed in the present study, can be attributed to the damaged structural integrity of liver cells and leakage of AST and ALT enzymes into circulation [35,36]. The tendency of these marker enzymes to return to near normalcy indicates hepatocyte regeneration [37].…”
Section: Antioxidant Activities and Liver Function Parameterssupporting
confidence: 72%
“…The etahnolic extract of C. oliviforme (Oe) could thus be considered as the most effective in reversing the harmful effect of CCl 4 -liver injury on ALT and AST raised levels when compared to the standard hepatoprotective drug, Silymarin with relative potencies 1.51 and 2.22, respectively ( Table 2). The raised activity of serum transaminases in CCl 4 intoxicated rats, as observed in the present study, can be attributed to the damaged structural integrity of liver cells and leakage of AST and ALT enzymes into circulation [35,36]. The tendency of these marker enzymes to return to near normalcy indicates hepatocyte regeneration [37].…”
Section: Antioxidant Activities and Liver Function Parameterssupporting
confidence: 72%
“…Several pro-apoptotic and anti-apoptotic proteins such as Bax and Bcl2 are responsible for cellular apoptosis [61][62][63][64]. Bax is an important pro-apoptotic gene in the Bcl2 family, which may translocate to the mitochondria to induce apoptosis [65], whereas Bcl2 is an anti-apoptotic protein that suppresses apoptosis [66,67]. In our study, we found that CCl 4 administration induced apoptosis of liver cells by significant elevation of cleaved caspase-3, cleaved caspase-9 and Bax expression while Bcl2 expression was inhibited, and these conditions were reversed in DIM pretreatment condition.…”
Section: Discussionmentioning
confidence: 99%
“…Bax is a key master apoptotic protein, while Bcl-2 is enemy of apoptosis. [61][62][63] Our realities demonstrated that CCl 4 persuaded observable apoptosis of liver cells, checked by the significant height of caspase-3 action. In concurrence with prior research, CCl 4 intensified Bax expression while diminished Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 61%
“…The family incorporates proapoptotic and against apoptotic individuals. Bax is a key master apoptotic protein, while Bcl‐2 is enemy of apoptosis . Our realities demonstrated that CCl 4 persuaded observable apoptosis of liver cells, checked by the significant height of caspase‐3 action.…”
Section: Discussionmentioning
confidence: 67%